Composite gas separation membranes, methods of making and using the same
Patent Information
- Application Number
- CN202510560744.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]本发明的目的是为了克服现有技术对PDMS改性中存在的改性效果稳定性差、工艺复杂、气体通量损失大等问题,提供一种复合气体分离膜及其制备方法和应用,该复合气体分离膜中依次包括多孔支撑层、疏水聚合物层、由具有特定结构的亲水聚合物形成的亲水聚合物层以及聚氧乙烯型聚合物分离层,疏水聚合物层作为中间层能够防孔渗提高气体渗透性,界面聚合改性层能够改善亲水性,进而有利于溶于极性溶剂的聚氧乙烯型聚合物在膜表面形成薄且致密的分离层,各层之间的相互配合,能够强化复合膜的层间相容性和气体渗透选择性
[0017]本发明提供的复合气体分离膜中依次包括多孔支撑层、疏水聚合物层、由具有特定结构的亲水聚合物形成的亲水聚合物层以及聚氧乙烯型聚合物分离层,疏水聚合物中间层能够实现防孔渗和提高气体渗透性,界面聚合亲水改性层能够解决分离层材料的极性溶剂在疏水中间层上难铺展的技术难题,分离层增强复合膜的气体选择性,上述四层相互配合,使得复合膜的综合性能较好。
Smart Images

Figure CN122999006A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer membrane materials and membrane separation technology, specifically to a composite gas separation membrane, its preparation method, and its application. Background Technology
[0002] With the continuous advancement of industrialization, the consumption of large quantities of fossil fuels has led to a sharp increase in carbon dioxide emissions, resulting in the greenhouse effect and causing problems such as global warming, frequent extreme weather events, and glacial melting. Membrane technology, due to its advantages of being environmentally friendly, low-cost, and simple to operate, has attracted widespread attention from researchers in gas separation fields such as air separation, hydrogen recovery, and carbon dioxide separation. Commercially available polyoxyethylene polymers such as polyether block polyamide (Pebax) and polyether block polybutylene terephthalate (Polyactive) are a class of membrane materials rich in ether oxygen groups. By enhancing the dissolution-diffusion mechanism, they show broad application prospects in the field of carbon dioxide membrane separation technology.
[0003] Different grades of Pebax materials sold by Arkema, a French company, are widely used by researchers in the study of carbon dioxide separation membranes. However, most research is limited to the preparation of micron-thick homogeneous membranes on a laboratory scale. In practical membrane separation applications, key membrane materials are typically used to prepare ultrathin separation layers, resulting in high-flux multilayer composite membranes. Multilayer composite membranes usually consist of an ultrathin separation layer, an intermediate layer, and a porous support. Inexpensive materials with good mechanical properties are used to prepare the porous support, while highly permeable polymers are often used to prepare the intermediate layer to suppress the permeation of the separation layer membrane material within the porous support and improve interlayer interface compatibility. The dense, ultrathin separation layer provides the main separation function. The layers of gas separation composite membranes in this technical field can be prepared using various methods, including phase inversion, interfacial polymerization, and coating methods.
[0004] Common interlayer materials are often inexpensive, film-forming, and highly permeable silane polymers, such as commercially available hydrophobic polymers like polydimethylsiloxane (PDMS) and poly(1-trimethylsilyl-1-propyne, PTMSP). The low surface energy of silane materials gives the membrane surface an inherent hydrophobic property. However, polyethylene oxide polymers typically require dissolution in polar solvents to prepare the casting solution, thereby creating an ultrathin, defect-free separation layer. Good spreading of the casting solution on the interlayer is crucial for achieving a defect-free ultrathin separation layer. Therefore, to achieve good spreading of polar solvents on a hydrophobic interlayer, hydrophilic modification of the hydrophobic surface is necessary. PDMS materials are widely used in gas separation and pervaporation membrane technologies, and there are numerous reports on the hydrophilic modification of PDMS. Common hydrophilic modification methods include chemical surface modification, crosslinking copolymerization to introduce hydrophilic side chains, UV-ozone treatment, and plasma treatment. Currently, the preparation of Pebax composite membranes by hydrophilic modification of PDMS using plasma technology has attracted considerable attention due to its shorter processing time and lower gas flux loss. Researchers both domestically and internationally have used oxygen plasma and air plasma technologies to hydrophilically modify PDMS (ACS Appl. Mater. Interfaces, 2020, 12:33196-33209; Journal of Membrane Science, 2022, 658, 120741; Journal of Membrane Science, 2023, 667, 121183; CN115608177B). The resulting Pebax composite membranes exhibit CO2 permeation rates of ~2000 GPU and CO2 / N2 selectivity of ~30.
[0005] Current publicly available technologies for hydrophilic modification of PDMS face challenges such as expensive and complex equipment, long modification processes, significant gas flux losses, and difficulty in industrial scale-up. Research on plasma-modified PDMS typically requires plasma modification under specific vacuum conditions, which is difficult to achieve in continuous industrial production and involves expensive equipment. Furthermore, short plasma treatment times only maintain the hydrophilicity of the PDMS surface for a limited period, while longer treatment times lead to the formation of dense SiO₂. x In the first layer, the gas flux of the membrane decreases significantly. By optimizing the existing hydrophilic modification process and controlling the structure of the Pebax separation layer, it is possible to achieve good spreading of the Pebax solution in PDMS and maintain the high gas permeability of the composite membrane. Summary of the Invention
[0006] The purpose of this invention is to overcome the problems of poor modification effect stability, complex process, and large gas flux loss in the existing technology of PDMS modification, and to provide a composite gas separation membrane, its preparation method and application. The composite gas separation membrane includes, in sequence, a porous support layer, a hydrophobic polymer layer, a hydrophilic polymer layer formed by a hydrophilic polymer with a specific structure, and a polyoxyethylene polymer separation layer. The hydrophobic polymer layer, as an intermediate layer, can prevent pore seepage and improve gas permeability. The interfacial polymerization modification layer can improve hydrophilicity, which is conducive to the formation of a thin and dense separation layer of polyoxyethylene polymer dissolved in polar solvents on the membrane surface. The cooperation between the layers can enhance the interlayer compatibility and gas permeation selectivity of the composite membrane.
[0007] To achieve the above objectives, the first aspect of the present invention provides a composite gas separation membrane, wherein the composite gas separation membrane comprises, in sequence, a porous support layer, a hydrophobic polymer layer, a hydrophilic polymer layer, and a polyoxyethylene polymer separation layer;
[0008] The hydrophilic polymer forming the hydrophilic polymer layer includes structural unit I from polyacrylamide chloride, structural unit II from polyamine containing ether bonds, and optionally structural unit III from hydroxyl-containing compounds;
[0009] In this structure, structural unit I and structural unit II are connected by amide bonds, and structural unit I and structural unit III are connected by ester groups.
[0010] A second aspect of the present invention provides a method for preparing a composite gas separation membrane, characterized in that the preparation method includes:
[0011] (1) A hydrophobic polymer layer is prepared on a porous support layer to obtain a composite membrane;
[0012] (2) After the composite membrane is first contacted with an organic phase containing polyacryl chloride and dried, it is then second contacted with an aqueous phase containing a polyamine containing an ether bond, optionally a hydroxyl compound, an acid absorbent and optionally a surfactant, and then heat-treated to obtain a hydrophilic modified composite membrane.
[0013] (3) The casting solution containing polyoxyethylene copolymer, optional additives and solvent is brought into a third contact with the hydrophilic modified composite membrane, and after drying, the composite gas separation membrane is obtained.
[0014] A third aspect of the present invention provides a composite gas separation membrane prepared by the above-described preparation method.
[0015] A fourth aspect of the present invention provides an application of the above-described composite gas separation membrane in the separation of gas mixtures.
[0016] Through the above technical solutions, the composite gas separation membrane, its preparation method, and its application provided by the present invention achieve the following beneficial effects:
[0017] The composite gas separation membrane provided by this invention comprises, in sequence, a porous support layer, a hydrophobic polymer layer, a hydrophilic polymer layer formed by a hydrophilic polymer with a specific structure, and a polyoxyethylene polymer separation layer. The hydrophobic polymer intermediate layer can prevent pore seepage and improve gas permeability. The interfacial polymer hydrophilic modification layer can solve the technical problem that the polar solvent of the separation layer material is difficult to spread on the hydrophobic intermediate layer. The separation layer enhances the gas selectivity of the composite membrane. The above four layers work together to make the composite membrane have good overall performance.
[0018] In the preparation method of the composite gas separation membrane provided by the present invention, an interfacial polymerization process is used to prepare a hydrophilic polymer layer on a hydrophobic polymer layer by placing polyacrylamide chloride, polyamine containing ether bonds, and optionally a hydroxyl-containing compound. The increased hydrophilicity is beneficial to the spread of polar solvent in the separation layer. A casting solution containing a polyoxyethylene copolymer is further coated on the hydrophilic polymer layer to form a thin and defect-free polyoxyethylene polymer separation layer. This not only improves the compatibility between the layers of the gas separation composite membrane, but also significantly reduces the thickness of the separation layer, thereby reducing the gas transmission resistance and increasing the gas permeation rate of the composite membrane.
[0019] Furthermore, based on the interfacial polymerization hydrophilic modified composite membrane, a casting solution containing specific additives and solvents is used to coat and modify the hydrophilic modified composite membrane. The specific additives and solvents significantly improve the solubility and film-forming properties of the polyoxyethylene copolymer, which not only improves the compatibility between the composite membrane layers, but also helps to achieve ultrathin separation layers of the polyoxyethylene polymer, thereby effectively reducing gas transmission resistance and further enhancing the gas permeation selectivity of the composite membrane.
[0020] Furthermore, compared to traditional hydrophilic modification techniques, the method for preparing the hydrophilic modified composite gas separation membrane provided by this invention utilizes interfacial polymerization to achieve hydrophilic modification of the hydrophobic polymer layer. This preparation method features simple equipment, easy operation, good technical and economic efficiency, and ease of industrial application. Attached Figure Description
[0021] Figure 1 The infrared spectra of the films prepared in Comparative Example 1, Comparative Example 2 and Example 1 are shown.
[0022] Figure 2 These are XPS spectra of the films prepared in Comparative Example 1, Comparative Example 2 and Example 1. Detailed Implementation
[0023] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0024] The first aspect of the present invention discloses a composite gas separation membrane, wherein the composite gas separation membrane comprises, in sequence, a porous support layer, a hydrophobic polymer layer, a hydrophilic polymer layer and a polyoxyethylene polymer separation layer;
[0025] The hydrophilic polymer forming the hydrophilic polymer layer includes structural unit I from polyacrylamide chloride, structural unit II from polyamine containing ether bonds, and optionally structural unit III from hydroxyl-containing compounds;
[0026] In this structure, structural unit I and structural unit II are connected by amide bonds, and structural unit I and structural unit III are connected by ester groups.
[0027] In this invention, the composite gas separation membrane sequentially comprises a porous support layer, a hydrophobic polymer layer, a hydrophilic polymer layer formed by a hydrophilic polymer with a specific structure, and a polyoxyethylene polymer separation layer. The hydrophobic polymer intermediate layer can prevent pore seepage and thus improve gas permeability. The interface polymerization hydrophilic modification layer can solve the technical problem that the polar solvent of the separation layer material is difficult to spread on the hydrophobic layer. The separation layer enhances the gas selectivity of the composite membrane. The above four layers work together to make the composite membrane have good overall performance.
[0028] Specifically, the composite gas separation membrane of the present invention comprises a hydrophilic polymer layer formed by a hydrophilic polymer with a specific structure. The hydrophilic polymer contains structural units from polyamines containing ether bonds, which can improve the hydrophilicity of the gas separation membrane surface while reducing defects in the gas separation membrane. At the same time, the improved hydrophilicity facilitates the subsequent spreading of polyoxyethylene polymer solutions on the membrane surface and is conducive to the formation of a thin and dense polyoxyethylene polymer separation layer, thereby improving the gas selectivity of the separation membrane.
[0029] In this invention, structural units I and III, which are connected by ester groups, form flexible polyester segments in the hydrophilic polymer, while structural units I and II, which are connected by amide bonds, form polyamide segments.
[0030] In this invention, the hydrophilic polymer is formed by linking structural units II from ether-containing polyamines and, optionally, structural units III from hydroxyl-containing compounds through structural unit I from polyacrylamide to form a random copolymer.
[0031] According to the present invention, the polyoxyethylene polymer separation layer comprises a polyoxyethylene polymer and optionally additives.
[0032] According to the present invention, the additive is a compound containing an ether bond.
[0033] In this invention, when the polyoxyethylene polymer separation membrane includes the above-mentioned ether-containing compound, the degree of polymer chain stacking can be controlled. At the same time, the ether bond has good carbon dioxide affinity, which can further enhance the gas permeation selectivity of the composite gas separation membrane.
[0034] In one specific embodiment of the present invention, the additive is selected from at least one of crown ether, cyclodextrin, polyoxyethylene ether, Tween, and polyethylene glycol.
[0035] In a preferred embodiment of the present invention, the additive is a cyclic supramolecular compound containing ether bonds. The cyclic structure in the additive can serve as a gas transfer channel, which can further enhance the gas permeability of the composite gas separation membrane.
[0036] In one specific embodiment of the present invention, the cyclic supramolecular compound containing ether bonds is selected from crown ethers and / or cyclodextrins.
[0037] According to the present invention, the mass ratio of the polyoxyethylene copolymer to the additive is 1:0 to 1:2.
[0038] In this invention, when the amount of additive meets the above range, the ether-containing additive can effectively control the packing density of the polyoxyethylene copolymer segments, improve gas permeation selectivity, and at the same time avoid the formation of poor membrane structure and the resulting decline in membrane performance when the amount of additive is too high.
[0039] Furthermore, the mass ratio of the polyoxyethylene copolymer to the additive is 1:0.1-1:1.
[0040] In this invention, there is no particular limitation on the type of polyoxyethylene copolymer (Pebax), which can be a conventional type of polyoxyethylene copolymer in the art, such as at least one of Pebax1074, Pebax1657, Pebax2533, Pebax3533 and Pebax5533.
[0041] According to the present invention, the polyacryl chloride is selected from at least one of oxaloyl chloride, adipicoyl chloride, cyclohexanoyl chloride, terephthaloyl chloride, isophthaloyl chloride and trimesoyl chloride, preferably selected from isophthaloyl chloride and / or trimesoyl chloride.
[0042] According to the present invention, the polyamine containing ether bonds is selected from at least one of polyoxyethylene diamine, ethylene glycol bis(3-aminopropyl) ether, polyetheramine and diethylene glycol bis(3-aminopropyl) ether.
[0043] According to the present invention, the hydroxyl-containing compound is selected from at least one of polyvinyl alcohol, (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and water-soluble polymeric cyclodextrin.
[0044] In this invention, a hydrophilic polymer layer is formed on the surface of a hydrophobic polymer layer by interfacial polymerization of polyacrylamide chloride, polyamine containing ether bonds, and optionally hydroxyl-containing compounds.
[0045] In a preferred embodiment of the present invention, in order to reduce the gas transmission resistance of the interfacial polymerization modified layer, a cyclodextrin compound containing a 3D cavity is introduced into the hydrophilic polymer layer, which can further improve the permeability of the hydrophilic polymer layer. The cyclodextrin compound containing a 3D cavity is selected from at least one of (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and water-soluble polymeric cyclodextrin.
[0046] According to the present invention, the polymer forming the hydrophobic polymer layer is selected from polydimethylsiloxane and / or polydimethylsiloxane-polyoxyethylene copolymer.
[0047] In this invention, the content of carbon atoms on the surface of the composite gas separation membrane, as measured by XPS, is 55-80 at, the content of nitrogen atoms is 0.1-10 at, the content of oxygen atoms is 10-35 at, and the content of silicon atoms is 0-2 at.
[0048] In this invention, the type of porous support layer is not particularly limited, and it can be made of various existing materials with certain strength that can be used in ultrafiltration membranes. Preferably, the porous support layer comprises a bottom layer and a porous intermediate layer. The bottom layer is a non-woven fabric material, preferably polyester and / or polyolefin. The porous intermediate layer can be made of at least one of polyvinylidene fluoride, polypropylene, cellulose acetate, polyethylene, polytetrafluoroethylene, polyetherimide, polyimide, polyacrylonitrile, polyethersulfone, and polysulfone.
[0049] In this invention, there is no particular limitation on the source of the porous support layer. It can be commercially available, or the porous layer can be prepared at the bottom layer according to conventional preparation methods in the art, such as phase transformation method, to obtain the porous support layer.
[0050] In this invention, there are no special requirements for the thickness of the porous support layer. For example, the thickness of the porous support layer is 20-200 μm.
[0051] According to the present invention, the thickness of the hydrophobic polymer layer is 50-300 nm.
[0052] According to the present invention, the thickness of the hydrophilic polymer layer is 50-500 nm.
[0053] According to the present invention, the thickness of the polyoxyethylene copolymer separation layer is 50-300 nm.
[0054] In this invention, when the thicknesses of the hydrophobic polymer layer, the hydrophilic polymer layer, and the polyoxyethylene copolymer separation layer in the gas separation membrane each independently meet the above-mentioned ranges, the composite membrane can still maintain a high gas permeation selectivity.
[0055] Furthermore, the thickness of the hydrophobic polymer layer is 80-150 nm.
[0056] Furthermore, the thickness of the hydrophilic polymer layer is 90-200 nm.
[0057] Furthermore, the thickness of the polyoxyethylene copolymer separation layer is 50-150 nm.
[0058] A second aspect of the present invention provides a method for preparing a composite gas separation membrane, wherein the preparation method includes:
[0059] (1) A hydrophobic polymer layer is prepared on a porous support layer to obtain a composite membrane;
[0060] (2) After the composite membrane is first contacted with an organic phase containing polyacryl chloride and dried, it is then second contacted with an aqueous phase containing a polyamine containing an ether bond, optionally a hydroxyl compound, an acid absorbent and optionally a surfactant, and then heat-treated to obtain a hydrophilic modified composite membrane.
[0061] (3) The casting solution containing polyoxyethylene copolymer, optional additives and solvent is brought into a third contact with the hydrophilic modified composite membrane, and after drying, the composite gas separation membrane is obtained.
[0062] In this invention, an interfacial polymerization process is used to prepare a hydrophilic polymer layer by depositing polyacrylamide chloride, polyamine containing ether bonds, and optionally hydroxyl-containing compounds on a hydrophobic polymer layer. The increased hydrophilicity is beneficial to the spread of polar solvents in the separation layer. A casting solution containing a polyoxyethylene copolymer is further coated on the hydrophilic polymer layer to form a thin and defect-free polyoxyethylene copolymer separation layer. This not only improves the compatibility between the layers of the gas separation composite membrane, but also significantly reduces the thickness of the separation layer of the prepared gas separation membrane, thereby reducing gas transmission resistance and increasing the gas permeation rate of the composite membrane.
[0063] Furthermore, compared to traditional hydrophilic modification techniques, the method for preparing the hydrophilic composite gas separation membrane provided by this invention utilizes interfacial polymerization to achieve hydrophilic modification of the hydrophobic polymer layer. This preparation method features simple equipment, easy operation, good technical and economic efficiency, and ease of industrial application.
[0064] According to the present invention, in step (3), the concentration of the polyoxyethylene copolymer in the casting solution is 0.01-3 wt%; and the concentration of the additive is 0-1 wt%.
[0065] In this invention, when the concentrations of the polyoxyethylene copolymer and the additives in the casting solution independently meet the above-mentioned ranges, the composite membrane exhibits good spreadability on the interfacial polymer hydrophilic modified layer, while the polyoxyethylene polymer separation layer containing the additives has a good chain segment stacking structure, and the composite membrane has good permeation selectivity.
[0066] Furthermore, the concentration of the polyoxyethylene copolymer in the casting solution is 0.1-1 wt%, and the concentration of the additive is 0.1-0.5 wt%.
[0067] According to the present invention, the additive is a compound containing an ether bond.
[0068] In this invention, when the polyoxyethylene copolymer separation membrane includes the above-mentioned ether-containing compound, the degree of polymer chain stacking can be controlled. At the same time, the ether bond has good carbon dioxide affinity, which can further enhance the gas permeation selectivity of the composite gas separation membrane.
[0069] In one specific embodiment of the present invention, the additive is selected from at least one of crown ether, cyclodextrin, polyoxyethylene ether, Tween, and polyethylene glycol.
[0070] In a preferred embodiment of the present invention, the additive is a cyclic supramolecular compound containing ether bonds. The cyclic structure in the additive can serve as a gas transfer channel, which can further enhance the gas permeability of the composite gas separation membrane.
[0071] In one specific embodiment of the present invention, the cyclic supramolecular compound containing ether bonds is selected from crown ethers and / or cyclodextrins.
[0072] According to the present invention, in step (3), the solvent is selected from at least one of water, methanol, ethanol, isopropanol, and n-butanol.
[0073] In this invention, the selection of the aforementioned specific types of solvents can work in conjunction with additives to further improve the solubility and film-forming properties of polyoxyethylene copolymers. This not only enhances the compatibility between composite membrane layers but also facilitates the ultrathinning of the polyoxyethylene copolymer separation layer, thereby effectively reducing gas transmission resistance and further enhancing the gas permeation selectivity of the composite membrane.
[0074] In a preferred embodiment of the present invention, the solvent is selected from at least one of n-butanol, a mixture of ethanol and water, a mixture of n-butanol and ethanol, and a ternary mixture of n-butanol, ethanol, and water.
[0075] In one specific embodiment of the present invention, the solvent is a mixture of ethanol and water, wherein the volume ratio of ethanol to water is 2-8:1. In the present invention, when the volume ratio of ethanol to water is controlled to meet the above range, it has good Pebax solubility and film-forming properties, and the volatility of the solvent is beneficial to improving gas permeability. Preferably, the volume ratio of ethanol to water is 2-6:1.
[0076] In another specific embodiment of the present invention, the solvent is a mixture of n-butanol and ethanol, wherein the volume ratio of n-butanol to ethanol is 3-10:1, preferably 5-9:1.
[0077] In another specific embodiment of the present invention, the solvent is a ternary mixture of n-butanol, ethanol and water, wherein the volume ratio of n-butanol, ethanol and water is 1-9:1-5:1, preferably 5-9:1-3:1.
[0078] In a preferred embodiment of the present invention, a casting solution is prepared by pre-mixing a polyoxyethylene copolymer, optionally an additive, and a solvent under stirring conditions. Pre-preparing the casting solution ensures that the polyoxyethylene copolymer and optionally the additive are fully dissolved and uniformly mixed, facilitating subsequent coating of the casting solution onto the hydrophilic modified composite membrane.
[0079] Specifically, the mixing temperature is 70-90℃, and the mixing time is 0.2-6h.
[0080] In this invention, preferably, after mixing, the casting solution is allowed to stand at room temperature for 2-24 hours.
[0081] In this invention, there are no particular limitations on the contact method between the casting solution and the hydrophilic modified composite membrane. Conventional contact methods in the art can be used. Preferably, in order to improve the coating performance of the casting solution on the hydrophilic modified composite membrane, the third contact is performed by dip coating.
[0082] According to the present invention, the dip-coating time is 5s-180s, and the dip-coating temperature is 10-60℃.
[0083] In this invention, when the dipping time and temperature are controlled within the above range, the casting solution can fully contact and wet the membrane surface to form a dense and defect-free separation layer, and the composite membrane obtains better permeation separation performance.
[0084] Furthermore, the dip-coating time is 10s-60s, and the dip-coating temperature is 15-35℃.
[0085] In this invention, there is no particular limitation on the ratio of the volume of the casting solution to the area of the hydrophilic modified composite membrane, which can be adjusted according to actual process conditions. For example, the ratio of the volume of the casting solution to the area of the hydrophilic modified composite membrane is 0.05-3 mL / cm². 2 Preferably 0.1-1 mL / cm 2 .
[0086] In this invention, there are no particular limitations on the drying conditions in step (3), as long as the product after the third contact is sufficiently dried.
[0087] According to the present invention, the concentration of polyacrylamide chloride in the organic phase is 0.025-0.3 wt%.
[0088] Furthermore, the concentration of polyacrylamide chloride in the organic phase is 0.05-0.2 wt%.
[0089] According to the present invention, the polyacryl chloride is selected from at least one of oxaloyl chloride, adipicoyl chloride, cyclohexanoyl chloride, terephthaloyl chloride, isophthaloyl chloride and trimesoyl chloride, preferably selected from isophthaloyl chloride and / or trimesoyl chloride.
[0090] In this invention, there is no particular limitation on the volume ratio of the organic phase to the area of the composite membrane, which can be adjusted according to actual process conditions. For example, the volume ratio of the organic phase to the area of the composite membrane can be 0.1-3 mL / cm². 2 Preferably, it is 0.2-1.5 mL / cm 2 .
[0091] In this invention, there is no particular limitation on the type of organic solvent in the organic phase. It can be a conventional type of organic solvent in the art, such as n-hexane, cyclohexane, cyclopentane, n-heptane, isoparaffins Isopar E, Isopar G, etc. Preferably, the organic solvent is selected from n-hexane and / or n-heptane.
[0092] According to the present invention, the concentration of the polyamine containing ether bonds in the aqueous phase is 0.02-1 wt%, the concentration of the hydroxyl-containing compound is 0-0.1 wt%, the concentration of the acid absorbent is 0.1-1 wt%, and the concentration of the surfactant is 0-0.3 wt%.
[0093] Further, the concentration of the polyamine containing ether bonds in the aqueous phase is 0.08-0.3 wt%, the concentration of the hydroxyl-containing compound is 0.02-0.08 wt%, the concentration of the acid absorbent is 0.3-0.9 wt%, and the concentration of the surfactant is 0.05-0.2 wt%.
[0094] According to the present invention, the polyamine containing ether bonds is selected from at least one of polyoxyethylene diamine, ethylene glycol bis(3-aminopropyl) ether, polyetheramine and diethylene glycol bis(3-aminopropyl) ether.
[0095] According to the present invention, the hydroxyl-containing compound is selected from at least one of polyvinyl alcohol, (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and water-soluble polymeric cyclodextrin, preferably selected from at least one of (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and water-soluble polymeric cyclodextrin.
[0096] In one specific embodiment of the present invention, the hydroxyl-containing compound is (2-hydroxypropyl)-β-cyclodextrin.
[0097] According to the present invention, the acid absorbent is selected from at least one of triethylamine, sodium hydroxide, sodium bicarbonate and sodium carbonate.
[0098] In a preferred embodiment of the present invention, the acid absorbent is selected from triethylamine and / or sodium carbonate.
[0099] According to the present invention, the surfactant is a nonionic surfactant.
[0100] In this invention, when a nonionic surfactant is used, it has a smaller effect on the ions of monomers in the aqueous phase, so that the monomers in the aqueous phase maintain good activity and reactivity, which is more conducive to regulating the interfacial polymerization reaction.
[0101] Furthermore, the surfactant is selected from at least one of Tween, polyoxyethylene ether, and polyethylene glycol, preferably polyethylene glycol.
[0102] In this invention, there is no particular limitation on the ratio of the volume of the aqueous phase to the area of the composite membrane, which can be adjusted according to actual process conditions. For example, the ratio of the volume of the aqueous phase to the area of the composite membrane can be 0.1-3 mL / cm². 2 Preferably, it is 0.2-1.5 mL / cm 2 .
[0103] In this invention, there is no particular limitation on the type of solvent in the aqueous phase; for example, it can be water.
[0104] According to the present invention, the duration of the first contact is 30-300 seconds.
[0105] Furthermore, the duration of the first contact is 30-200 seconds.
[0106] According to the present invention, the temperature of the first drying is 10-60°C.
[0107] Furthermore, the temperature of the first drying process is 15-35°C.
[0108] In this invention, there is no particular limitation on the first drying method, such as forced air drying.
[0109] According to the present invention, the conditions for the second contact include: a contact time of 10-300 s and a contact temperature of 15-55 °C.
[0110] In this invention, by controlling the conditions of the second contact to meet the above-mentioned range, it is possible for polyacrylamide chlorides, polyamines containing ether bonds, and optionally hydroxyl-containing compounds to undergo interfacial polymerization reactions on the surface of the composite film to form a hydrophilic polymer layer.
[0111] Furthermore, the conditions for the second contact include: a contact time of 60-180 seconds and a contact temperature of 20-50°C.
[0112] According to the present invention, the heat treatment conditions include: a heat treatment temperature of 40-80°C and a heat treatment time of 0-20 min.
[0113] Furthermore, the heat treatment conditions include: a heat treatment temperature of 40-60℃ and a heat treatment time of 5-10 minutes.
[0114] In this invention, the product after the second contact in step (2) is pre-washed and then heat-treated to remove unreacted monomers, so that the hydrophilic modified composite gas separation membrane maintains high gas permeability.
[0115] According to the present invention, the detergent for washing is selected from water and / or alcohol.
[0116] Furthermore, when the detergent is a mixture of water and alcohol, the volume ratio of water to alcohol is 1:0.5-10, preferably 1:1-5.
[0117] In this invention, there is no particular limitation on the type of alcohol, and it can be any alcohol commonly used in the art, such as methanol and / or ethanol.
[0118] According to the present invention, the washing is repeated 0-5 times, preferably 1-3 times.
[0119] In this invention, there are no particular limitations on the method for preparing the hydrophobic polymer layer on the porous support layer; conventional methods in the art can be used.
[0120] In a preferred embodiment of the present invention, the method for preparing a hydrophobic polymer layer on a porous support layer includes:
[0121] The composite membrane is obtained by coating a hydrophobic polymer solution onto a porous support layer and then drying it.
[0122] According to the present invention, the concentration of the hydrophobic polymer solution is 0.01-0.5 wt%.
[0123] In this invention, when the concentration of the hydrophobic polymer solution is controlled to meet the above-mentioned range, the coating is performed at a lower concentration of the hydrophobic polymer solution, which can avoid the adverse reduction in the gas permeability of the gas separation membrane due to the excessive thickness of the hydrophobic polymer layer.
[0124] Furthermore, the concentration of the hydrophobic polymer solution is 0.02-0.5 wt%.
[0125] In this invention, the ratio of the volume of the hydrophobic polymer solution to the area of the porous support layer is not particularly limited and can be adjusted according to the actual process. For example, the ratio of the volume of the hydrophobic polymer solution to the area of the porous support layer is 0.001-1 mL / cm². 2 Preferably, it is 0.005-0.5 mL / cm 2 .
[0126] According to the present invention, the hydrophobic polymer is selected from polydimethylsiloxane and / or polydimethylsiloxane-polyoxyethylene copolymer.
[0127] In this invention, there are no particular limitations on the drying conditions after coating the porous support layer with the hydrophobic polymer solution; conventional drying conditions in the art are sufficient.
[0128] In one specific embodiment of the present invention, the composite gas separation membrane is prepared according to the following method:
[0129] (i) The composite membrane is obtained by coating a hydrophobic polymer solution onto a porous support layer and then drying it;
[0130] (ii) After the composite membrane is first contacted with an organic phase containing polyacryl chloride and dried, it is then second contacted with an aqueous phase containing a polyamine containing an ether bond, optionally a hydroxyl compound, an acid absorbent and optionally a surfactant, and then heat-treated to obtain the hydrophilic modified composite membrane.
[0131] (iii) The casting solution containing a polyoxyethylene copolymer, optional additives and solvent is brought into a third contact with the hydrophilic modified composite membrane, and after drying, the composite gas separation membrane is obtained.
[0132] A third aspect of the present invention provides a composite gas separation membrane prepared by the above method.
[0133] A fourth aspect of the present invention provides an application of the above-mentioned composite gas separation membrane in the separation or purification of gas mixtures.
[0134] In this invention, the composite gas separation membrane is preferably suitable for the purification of nitrogen, oxygen, and carbon dioxide, and is also suitable for the separation of gas mixtures, including but not limited to the separation of two or more mixed gases from nitrogen, oxygen, carbon dioxide, sulfur dioxide, methane, ethylene, propylene, ethanol, propanol, butanol, and water vapor.
[0135] The present invention will be described in detail below through embodiments.
[0136] (1) Gas separation performance testing: Important performance indicators for evaluating gas separation membranes include permeability coefficient (P), permeation rate (R), and separation coefficient (α). The gas permeability coefficient P evaluates the ease with which gas permeates through the membrane and is usually used to characterize the gas permeability of the membrane material itself. The unit is Barrer (1 Barrer = 10⁻⁶). -10 cm 3 (STP)cm / (cm 2 For flat-sheet composite membranes, considering the influence of functional layer thickness, the gas permeation rate is usually used to evaluate the membrane's permeation performance. The unit of gas permeation rate R is GPU (1 GPU = 10⁻⁶). -6 cm 3 (STP) / (cm 2 The permeation rate (·s·cmHg) reflects the rate at which gas components permeate through the membrane and is used to characterize the permeability of gases during membrane processing. The separation coefficient α is the ratio of the permeation rates of two gases through the membrane; α is dimensionless and is used to characterize the selective permeability of gas components within the membrane.
[0137] (2) Physicochemical characterization of the membrane: After interfacial polymerization modification, nitrogen and corresponding functional groups of polyamide are present on the membrane surface, and the membrane thickness also increases. Compared with the comparative example, the Si and N characteristic peaks on the membrane surface weaken after coating with Pebax solution, while the C and O characteristic peaks are more intense. To verify the changes in the chemical structure of the composite membrane before and after interfacial modification and before and after coating with Pebax solution, the chemical structure of the membrane samples was characterized using an attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) and an X-ray photoelectron spectroscopy (XPS) instrument from Thermo Scientific, USA. In addition, the surface and cross-sectional structure of the membrane were characterized using a scanning electron microscope (SEM) from Hitachi, Japan, and the thickness of each layer of the composite membrane was measured.
[0138] All raw materials used in the examples and comparative examples are commercially available products.
[0139] Example 1
[0140] S1, In the polysulfone porous support layer (thickness 50μm, area 180cm²) 2 A 90 mL PDMS solution with a concentration of 0.05 wt% was coated onto the surface, and after drying, a composite membrane was formed.
[0141] S2. Prepare an organic phase solution containing 0.12 wt% trimesoyl chloride using n-heptane;
[0142] S3. Prepare an aqueous solution containing 0.08 wt% diethylene glycol bis(3-aminopropyl) ether, 0.06 wt% (2-hydroxypropyl)-β-cyclodextrin, 0.45 wt% sodium carbonate, and 0.05 wt% polyethylene glycol using deionized water;
[0143] S4. After the composite membrane is first contacted with 90 mL of the organic phase solution from step S2 for 120 s, it is dried by blowing air at 60 °C. Then, it is contacted with 90 mL of the aqueous phase solution from step S3 at 30 °C for 120 s, washed once with deionized water, and then washed twice with ethanol. The washed composite membrane is then heat-treated at 50 °C for 8 min to obtain the hydrophilic modified composite membrane.
[0144] S5. Prepare a solution containing 0.5 wt% Pebax2533 and 0.20 wt% crown ether (18-crown ether-6) using n-butanol, stir at 80°C for 1 h to dissolve it evenly, and let it stand for 12 h to obtain the casting solution.
[0145] S6. Use 90 mL of the casting solution from step S5 to dip-coat the hydrophilic modified composite membrane obtained in step S4. The dipping time is 30 s and the dipping temperature is 30 ℃. Then dry at 30 ℃ for 6 h to obtain composite gas separation membrane A1.
[0146] The infrared spectrum of the composite gas separation membrane A1 is as follows: Figure 1 As shown, by Figure 1 It can be seen that the composite membrane after interfacial polymerization and hydrophilic modification exhibits a significant 1651 cm⁻¹ thickness. -1 and 1536cm -1 The characteristic peak of amide is at 2927 cm⁻¹. -1 The characteristic peaks of the alkyl groups in the PDMS segment are significantly weakened. (XPS spectrum of the composite gas separation membrane is shown below.) Figure 2 As shown, by Figure 2It can be seen that the membrane surface after interfacial polymerization and hydrophilic modification exhibits a distinct N characteristic peak, while the Si characteristic peak of the PDMS layer weakens significantly. After coating with the Pebax layer, both the N and Si characteristic peaks weaken further. The weak Si characteristic peak indicates that some silane segments are embedded in the hydrophilic polymer layer and the Pebax separation layer, suggesting good interlayer compatibility between the separation layer, the hydrophilic polymer-modified layer, and the hydrophobic polymer layer (PDMS layer). Furthermore, the coating with the separation layer shows distinct C and O characteristic peaks, and the weakening of the N characteristic peak is similar to the reported Pebax elemental content (approximately 1.5% N in Pebax 2533) in the literature, indicating that a Pebax layer was successfully prepared on the polyamide layer generated by interfacial polymerization modification.
[0147] Example 2
[0148] S1, In the polysulfone porous support layer (thickness 50μm, area 180cm²) 2 A composite membrane is formed by coating 90 mL of 0.03 wt% PDMS solution onto the surface and drying it.
[0149] S2. Prepare an organic phase solution containing 0.15 wt% trimesoyl chloride using n-heptane;
[0150] S3. Prepare an aqueous solution containing 0.05 wt% diethylene glycol bis(3-aminopropyl) ether, 0.05 wt% hydroxypropyl-α-cyclodextrin, 0.60 wt% sodium carbonate, and 0.10 wt% polyethylene glycol using deionized water;
[0151] S4. After the composite membrane is first contacted with 90 mL of the organic phase solution from step S2 (contact time is 300 s), it is dried by blowing air at 35 °C; then it is contacted with 90 mL of the aqueous phase solution from step S3 at 50 °C for 300 s, and then washed once with deionized water and twice with ethanol; the cleaned composite membrane is heat-treated at 80 °C for 10 min to obtain the hydrophilic modified composite membrane.
[0152] S5. Prepare a solution containing 0.20 wt% Pebax1657 and 0.10 wt% hydroxypropyl-β-cyclodextrin using ethanol-water (ethanol to water volume ratio of 2.3:1). Stir at 80°C for 0.5 h to dissolve the solution evenly and let it stand for 6 h to obtain the casting solution.
[0153] S6. Use 90 mL of the casting solution from step S5 to dip-coat the hydrophilic modified composite obtained in step S4 for 60 s at a temperature of 35 °C, and then dry it at 60 °C for 3 h to obtain the composite gas separation membrane A2.
[0154] Example 3
[0155] S1, In the polysulfone porous support layer (thickness 50μm, area 180cm²) 2 A composite film is formed by coating 90 mL of 0.08 wt% PDMS solution onto the surface and drying it.
[0156] S2. Prepare an organic phase solution containing 0.20 wt% trimesoyl chloride using n-heptane;
[0157] S3. Prepare an aqueous solution containing 0.05 wt% polyoxyethylene diamine, 0.02 wt% water-soluble polymeric cyclodextrin, 0.10 wt% sodium carbonate, and 0.05 wt% polyoxyethylene ether using deionized water;
[0158] S4. After the composite membrane is first contacted with 90 mL of the organic phase solution from step S2 (contact time is 30 s), it is dried by blowing air at 15 °C; then it is contacted with 90 mL of the aqueous phase solution from step S3 at 20 °C for 60 s, and then washed with deionized water 5 times; the washed composite membrane is heat-treated at 40 °C for 20 min, and then dried to obtain the hydrophilic modified composite membrane.
[0159] S5. Prepare a solution containing 0.2wt% Pebax5533 and 0.1wt% polyethylene glycol using n-butanol-methanol (n-butanol to methanol volume ratio of 9:1), stir at 80℃ for 1h to dissolve it uniformly, and let it stand for 12h to obtain the casting solution.
[0160] S6. Use 90 mL of the casting solution from step S5 to dip and coat the hydrophilic modified composite membrane obtained in step S4. The dipping time is 180 s and the dipping temperature is 50 ℃. Then dry at 50 ℃ for 12 h to obtain composite gas separation membrane A3.
[0161] Example 4
[0162] S1 is the same as step S1 in Example 1;
[0163] S2 is the same as step S2 in Example 1;
[0164] S3 is the same as step S3 in Example 1;
[0165] S4 is the same as step S4 in Example 1;
[0166] S5. Prepare a solution containing 0.50 wt% Pebax2533 using n-butanol, stir at 80°C for 1 h to dissolve it evenly, and let it stand for 12 h to obtain the casting solution.
[0167] S6. Same as step S6 in Example 1, to obtain composite gas separation membrane A4.
[0168] Example 5
[0169] S1 is the same as step S1 in Example 1;
[0170] S2 is the same as step S2 in Example 1;
[0171] S3 is the same as step S3 in Example 1;
[0172] S4 is the same as step S4 in Example 1;
[0173] S5. Prepare a 0.50 wt% Pebax 2533 solution using n-butanol-ethanol (n-butanol to ethanol volume ratio of 9:1), otherwise the same as step S5 in Example 1;
[0174] S6. Same as step S6 in Example 1, to obtain composite gas separation membrane A5.
[0175] Example 6
[0176] S1 is the same as step S1 in Example 1;
[0177] S2 is the same as step S2 in Example 1;
[0178] S3 is the same as step S3 in Example 1;
[0179] S4 is the same as step S4 in Example 1;
[0180] S5. Prepare a solution containing 0.50 wt% Pebax2533 and 0.20 wt% polyoxyethylene ether using n-butanol-ethanol (n-butanol to ethanol volume ratio of 9:1), otherwise the same as step S5 in Example 1;
[0181] S6. Same as step S6 in Example 1, to obtain composite gas separation membrane A6.
[0182] Example 7
[0183] S1 is the same as step S1 in Example 1;
[0184] S2 is the same as step S2 in Example 1;
[0185] S3 is the same as step S3 in Example 1;
[0186] S4 is the same as step S4 in Example 1;
[0187] S5. Prepare a solution containing 0.50 wt% Pebax2533 and 0.20 wt% hydroxypropyl-β-cyclodextrin using n-butanol-ethanol-water (n-butanol, ethanol and water volume ratio of 8:1:1), otherwise the same as step S5 in Example 1;
[0188] S6. Same as step S6 in Example 1, to obtain composite gas separation membrane A7.
[0189] Example 8
[0190] S1 is the same as step S1 in Example 1;
[0191] S2 is the same as step S2 in Example 1;
[0192] S3 is the same as step S3 in Example 1;
[0193] S4 is the same as step S4 in Example 1;
[0194] S5. Prepare a solution containing 0.50 wt% Pebax1657 using ethanol-water (ethanol to water volume ratio of 2.3:1), otherwise the same as step S5 in Example 1;
[0195] S6. Same as step S6 in Example 1, to obtain composite gas separation membrane A8.
[0196] Example 9
[0197] S1 is the same as step S1 in Example 1;
[0198] S2 is the same as step S2 in Example 1;
[0199] S3 is the same as step S3 in Example 1;
[0200] S4 is the same as step S4 in Example 1;
[0201] S5. Prepare a solution containing 0.50 wt% Pebax1657 and 0.20 wt% hydroxypropyl-β-cyclodextrin using ethanol-water (ethanol to water volume ratio of 2.3:1), otherwise the same as step S5 in Example 1;
[0202] S6. Same as step S6 in Example 1, to obtain composite gas separation membrane A9.
[0203] Example 10
[0204] S1 is the same as step S1 in Example 1;
[0205] S2 is the same as step S2 in Example 1;
[0206] S3 is the same as step S3 in Example 1;
[0207] S4 is the same as step S4 in Example 1;
[0208] S5. Prepare a solution containing 0.50 wt% Pebax 1657 and 0.20 wt% ethylenediamine using ethanol-water (ethanol to water volume ratio of 2.3:1), otherwise the same as step S5 in Example 1;
[0209] S6. Same as step S6 in Example 1, to obtain composite gas separation membrane A10.
[0210] Example 11
[0211] S1 is the same as step S1 in Example 1;
[0212] S2 is the same as step S2 in Example 1;
[0213] S3 is the same as step S3 in Example 1;
[0214] S4 is the same as step S4 in Example 1;
[0215] S5. Prepare a solution containing 0.50 wt% Pebax1657 and 0.20 wt% hydroxypropyl-β-cyclodextrin using ethanol-water (ethanol to water volume ratio of 4:1), otherwise the same as step S5 in Example 1;
[0216] S6. Same as step S6 in Example 1, to obtain composite gas separation membrane A11.
[0217] Comparative Example 1
[0218] A gas separation membrane was prepared according to the method of Example 1, except that only step S1 was performed and the concentration of the PDMS polymer solution was 0.05 wt%, thus obtaining gas separation membrane D1.
[0219] The infrared spectrum of gas separation membrane D1 is as follows Figure 1 As shown, by Figure 1 As can be seen, there are no amide characteristic peaks. The XPS spectrum of the gas separation membrane is as follows: Figure 2 As shown, by Figure 2 It can be seen that the unmodified PDMS layer only shows characteristic peaks of C, O, and Si.
[0220] Comparative Example 2
[0221] The composite gas separation membrane was prepared according to the method in Example 1, except that:
[0222] Without performing step S5, only performing steps S1-S4 yields a hydrophilic modified composite membrane, denoted as composite gas separation membrane D2.
[0223] The infrared spectrum of the composite gas separation membrane D2 is as follows: Figure 1 As shown, by Figure 1 The characteristic peaks of amide groups are clearly visible. The XPS spectrum of the composite gas separation membrane is shown below. Figure 2 As shown, by Figure 2 It can be seen that the Si characteristic peak is significantly weakened, while the N characteristic peak indicates that the interfacial polymerization reaction has generated polyamide segments.
[0224] The thickness of each layer of the gas composite separation membrane prepared in the examples and comparative examples was tested, and the results are shown in Table 1.
[0225] Table 1
[0226] Hydrophobic polymer layer hydrophilic polymer layer Polyoxyethylene polymer layer unit nm nm nm Example 1 110 87 90 Example 2 80 95 80 Example 3 115 109 85 Example 4 110 90 92* Example 5 105 92 125* Example 6 108 88 86 Example 7 112 91 93 Example 8 110 90 115* Example 9 109 94 95 Example 10 110 90 82 Example 11 107 89 88 Comparative Example 1 110 - - Comparative Example 2 110 105 -
[0227] * Contains no additives.
[0228] As can be seen from Table 1, the thickness of the PDMS hydrophobic polymer layer in the examples and comparative examples is about 110 nm, the thickness of the hydrophilic polymer layer formed by interfacial polymerization modification is about 95 nm, and the thickness of the polyoxyethylene polymer separation layer prepared after coating with polyoxyethylene polymer casting solution is about 100 nm. This indicates that by optimizing the structure of each layer of the composite membrane, the preparation of an ultrathin separation layer was achieved, which enhanced the gas permeation separation performance of the composite gas separation membrane.
[0229] The content of each atom on the surface of the gas composite separation membrane prepared in some embodiments and comparative examples was tested and analyzed, and the results are shown in Table 2.
[0230] Table 2
[0231] <![CDATA[C a ]]> <![CDATA[N a ]]> <![CDATA[O a ]]> <![CDATA[Si a ]]> unit at% at% at% at% Example 1 76.5 1.6 20.8 1.1 Example 4 77.9 2.5 18.4 1.2 Example 8 66.2 5.3 27.5 1.0 Example 9 65.1 4.8 28.6 1.5 Comparative Example 1 50.6 - 23.7 25.7 Comparative Example 2 65.2 5.3 25.9 3.6
[0232] a - Relative atomic content of XPS surface analysis results.
[0233] Table 2 shows that nitrogen (N) elements were observed on the film surface after interfacial polymerization hydrophilic modification, indicating the successful formation of the hydrophilic polymer layer containing amide structural units. Furthermore, the presence of a small amount of silicon (Si) after interfacial polymerization modification suggests that when the hydrophobic PDMS layer was covered by the hydrophilic polymer layer, a small number of silane segments were embedded in the hydrophilic polymer layer during the interfacial polymerization process, indicating good bonding and compatibility between the hydrophilic modified layer and the PDMS hydrophobic polymer layer. Compared to Comparative Example 2, the Si content was lower, below 2 at%, after coating with a polyoxyethylene polymer casting solution. The N content in Example 1 was also reduced, and the N content in Examples 1 and 4 was similar to the reported N content of Pebax 2533. The N content in Examples 8 and 9 was similar to the reported N content of Pebax 1657. Examples 1 and 9, using compounds containing ether bonds as additives, had higher oxygen (O) content compared to Examples 4 and 8, which did not contain additives. In summary, the composite gas separation membrane provided by this invention exhibits good bonding and compatibility among the polyoxyethylene polymer separation layer, the interfacially polymerized modified hydrophilic polymer layer, and the hydrophobic polymer layer. The hydrophilic modification facilitates the ultrathinning of the separation layer and improves the gas permeability of the composite membrane.
[0234] The gas permeation performance of the gas composite separation membranes prepared in the examples and comparative examples was tested, and the results are shown in Table 3.
[0235] Table 3
[0236]
[0237] As shown in Table 3, the embodiments using the multilayer composite membrane preparation technology provided by this invention exhibit good CO2 permeation selectivity. This is mainly because the interfacial polymerization hydrophilic modification layer facilitates the ultrathinning of the Pebax separation layer. Simultaneously, supramolecular additives such as crown ethers and cyclodextrins contain ether bonds with good CO2 affinity, and the cyclic structure of these additives can regulate and optimize the stacking of polymer segments, thereby enhancing the CO2 permeation selectivity of the composite membrane. This invention prepares a gas separation membrane with high permeation selectivity by coating an interfacial polymerization hydrophilic modification layer with a Pebax solution containing additives.
[0238] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A composite gas separation membrane, characterized in that, The composite gas separation membrane comprises, in sequence, a porous support layer, a hydrophobic polymer layer, a hydrophilic polymer layer, and a polyoxyethylene polymer separation layer; The hydrophilic polymer forming the hydrophilic polymer layer includes structural unit I from polyacrylamide chloride, structural unit II from polyamine containing ether bonds, and optionally structural unit III from hydroxyl-containing compounds; In this structure, structural unit I and structural unit II are connected by amide bonds, and structural unit I and structural unit III are connected by ester groups.
2. The composite gas separation membrane according to claim 1, wherein, The polyoxyethylene polymer separation layer includes a polyoxyethylene polymer and optional additives; Preferably, the additive is a compound containing an ether bond, and is preferably selected from at least one of crown ethers, cyclodextrins, polyoxyethylene ethers, Tween, and polyethylene glycol; Preferably, the mass ratio of the polyoxyethylene polymer to the additive is 1:0-1:2, and more preferably 1:0.1-1:
1.
3. The composite gas separation membrane according to claim 1 or 2, wherein, The polyacryl chloride is selected from at least one of oxaloyl chloride, adipicoyl chloride, cyclohexyl chloride, terephthaloyl chloride, isophthaloyl chloride and trimesoyl chloride, preferably selected from isophthaloyl chloride and / or trimesoyl chloride; Preferably, the polyamine containing ether bonds is selected from at least one of polyoxyethylene diamine, ethylene glycol bis(3-aminopropyl) ether, polyetheramine, and diethylene glycol bis(3-aminopropyl) ether; Preferably, the hydroxyl-containing compound is selected from at least one of polyvinyl alcohol, (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and water-soluble polymeric cyclodextrin, and more preferably from at least one of (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and water-soluble polymeric cyclodextrin.
4. The composite gas separation membrane according to any one of claims 1-3, wherein, The polymer forming the hydrophobic polymer layer is selected from polydimethylsiloxane and / or polydimethylsiloxane-polyoxyethylene copolymer.
5. The composite gas separation membrane according to any one of claims 1-4, wherein, The thickness of the hydrophobic polymer layer is 50-300 nm, preferably 80-150 nm; Preferably, the thickness of the hydrophilic polymer layer is 50-500 nm, and more preferably 90-200 nm; Preferably, the thickness of the polyoxyethylene polymer separation layer is 50-300 nm, and more preferably 50-150 nm.
6. A method for preparing a composite gas separation membrane, characterized in that, The preparation method includes: (1) A hydrophobic polymer layer is prepared on a porous support layer to obtain a composite membrane; (2) After the composite membrane is first contacted with an organic phase containing polyacryl chloride and dried, it is then second contacted with an aqueous phase containing a polyamine containing an ether bond, optionally a hydroxyl compound, an acid absorbent and optionally a surfactant, and then heat-treated to obtain a hydrophilic modified composite membrane. (3) The casting solution containing polyoxyethylene copolymer, optional additives and solvent is brought into a third contact with the hydrophilic modified composite membrane, and after drying, the composite gas separation membrane is obtained.
7. The preparation method according to claim 6, wherein, The concentration of the polyoxyethylene copolymer in the casting solution is 0.01-3 wt%, preferably 0.1-1 wt%; the concentration of the additive is 0-1 wt%, preferably 0.1-0.5 wt%. Preferably, the additive is a compound containing an ether bond, and is preferably selected from at least one of crown ethers, cyclodextrins, polyoxyethylene ethers, Tween, and polyethylene glycol; Preferably, the solvent in step (3) is selected from at least one of water, methanol, ethanol, isopropanol, and n-butanol, and more preferably from at least one of n-butanol, a mixture of ethanol and water, a mixture of n-butanol and ethanol, and a mixture of n-butanol, ethanol, and water.
8. The preparation method according to claim 6 or 7, wherein, The third contact method is dip coating; Preferably, the dip-coating time is 5s-180s, more preferably 10-60s; the dip-coating temperature is 10-60℃, more preferably 15-35℃.
9. The preparation method according to any one of claims 6-8, wherein, The concentration of polyacryl chloride in the organic phase is 0.025-0.3 wt%, preferably 0.05-0.2 wt%. Preferably, the polyacryl chloride is selected from at least one of oxaloyl chloride, adipicoyl chloride, cycloadipic chloride, terephthaloyl chloride, isophthaloyl chloride and trimesoyl chloride, and more preferably from isophthaloyl chloride and / or trimesoyl chloride.
10. The method according to any one of claims 6-9, wherein, The concentration of the polyamine containing ether bonds in the aqueous phase is 0.02wt%-1wt%, preferably 0.08-0.3wt%, the concentration of the hydroxyl-containing compound is 0-0.1wt%, preferably 0.02-0.08wt%, the concentration of the acid absorbent is 0.1-1wt%, preferably 0.3-0.9wt%, and the concentration of the surfactant is 0-0.3wt%, preferably 0.05-0.2wt%. Preferably, the polyamine containing ether bonds is selected from at least one of polyoxyethylene diamine, ethylene glycol bis(3-aminopropyl) ether, polyetheramine, and diethylene glycol bis(3-aminopropyl) ether; Preferably, the hydroxyl-containing compound is selected from at least one of polyvinyl alcohol, (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and water-soluble polymeric cyclodextrin, and more preferably from at least one of (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and water-soluble polymeric cyclodextrin; Preferably, the acid absorbent is selected from at least one of triethylamine, sodium hydroxide, sodium bicarbonate, and sodium carbonate; Preferably, the surfactant is a nonionic surfactant, and is preferably selected from at least one of Tween, polyoxyethylene ether, and polyethylene glycol.
11. The method according to any one of claims 6-10, wherein, The duration of the first contact is 30-300 seconds, preferably 30-200 seconds; Preferably, the drying temperature is 10-60℃, more preferably 15-35℃; Preferably, the conditions for the second contact include: a contact time of 10-300s, preferably 60-180s, and a contact temperature of 15-55℃, preferably 20-50℃. Preferably, the heat treatment conditions include: a heat treatment temperature of 40-80℃, more preferably 40-60℃, and a heat treatment time of 0-20min, more preferably 5-10min.
12. The method according to any one of claims 6-11, wherein, The method further includes: The product after the second contact in step (2) is washed; Preferably, the detergent for washing is selected from water and / or alcohol; Preferably, the washing is repeated 0-5 times, and more preferably 1-3 times.
13. The method according to any one of claims 6-12, wherein, Methods for preparing hydrophobic polymer layers on porous support layers include: The composite membrane is obtained by coating a hydrophobic polymer solution onto a porous support layer and then drying it. Preferably, the concentration of the hydrophobic polymer solution is 0.01-0.5 wt%. Preferably, the hydrophobic polymer is selected from polydimethylsiloxane and / or polydimethylsiloxane-polyoxyethylene copolymer.
14. A composite gas separation membrane prepared by the method according to any one of claims 6-13.
15. The application of the composite gas separation membrane according to any one of claims 1-5 and 14 in the separation of gas mixtures.
Citation Information
Patent Citations
A polyether block polyamide / polydimethylsiloxane composite gas separation membrane, its preparation method and application
CN115608177B
